2020
DOI: 10.1021/acsnano.0c02127
|View full text |Cite|
|
Sign up to set email alerts
|

Lectin-Glycan-Mediated Nanoparticle Docking as a Step toward Programmable Membrane Catalysis and Adhesion in Synthetic Protocells

Abstract: The spontaneous assembly of nanoscale building blocks into continuous semipermeable membranes is a key requirement for the structuration of synthetic protocells.Engineering the functionality and programmability of these building units provides a step towards more complex cell-like entities with adaptive membrane properties. Inspired by the central role of protein (lectin)-carbohydrate interactions in cellular recognition and adhesion, we fabricate semipermeable polysaccharide-polymer microcapsules (polysacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 48 publications
3
37
0
Order By: Relevance
“…Recently, Mukwaya et al covalently linked the Alexa Fluor 647-labeled WGA to polystyrene-co-polyacrylic acid, obtaining the 120 nm-diameter spherical nanoparticles. 44 Their experiments demonstrated that WGA recognized a GlcNAc-containing cell membrane mimic formed by semipermeable polysaccharide-polymer microcapsules. Duan et al engineered a WGA-conjugated, matrine-loaded nanoparticle that was able to target the HT-29 colon cancer cells in vitro.…”
Section: Potential Applications Of the Nanotechnique For Targeting O-...mentioning
confidence: 99%
“…Recently, Mukwaya et al covalently linked the Alexa Fluor 647-labeled WGA to polystyrene-co-polyacrylic acid, obtaining the 120 nm-diameter spherical nanoparticles. 44 Their experiments demonstrated that WGA recognized a GlcNAc-containing cell membrane mimic formed by semipermeable polysaccharide-polymer microcapsules. Duan et al engineered a WGA-conjugated, matrine-loaded nanoparticle that was able to target the HT-29 colon cancer cells in vitro.…”
Section: Potential Applications Of the Nanotechnique For Targeting O-...mentioning
confidence: 99%
“…[23] Those flexible interactions open up the possibility of reversible absorption and desorption, thus enabling the controllable release of attached molecules or Reproduced with permission. [3] Copyright 2020, American Chemical Society. B) Confocal microscopy images showing a mixture of three different populations of protein-stabilized droplets, fluorescein isothiocyanate-labeled bovine serum albumin (BSA-FITC,green), Rhodamine B labeled urease (urease-RBITC, red), and ATTO 425 Acid labeled glucose oxidase (GOx-Atto425, blue); scale bar in (a,b) = 100 ÎŒm; scale bar in (c) = 20 ÎŒm.…”
Section: Docked Decoration On Membranesmentioning
confidence: 99%
“…On the basis of the recognition and adhesion of protein (lectin)–polysaccharide, a new study shows that artificial cells (protocells) with a biomimetic membrane composed of polysaccharide copolymers can recognize lectins by using conjugates with lectin–glycan recognition sites as assembly units . Reversible docking of functional polymer nanoparticles on cell-like microcapsules was observed.…”
Section: Applicationsmentioning
confidence: 99%